IMPLEMENTATION OF MANHAJ MAQĀṢIDĪ BIN BAYAH IN UNDERSTANDING HADITH (FIQH ḤADĪṠ) - Kholishudin, Kholishudin; Ilmi, Moh. Hudal Hafid (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
Abdullah Bin Bayah is one of the international level ulama’ with multiple expertise. He offers the use of maqāṣid kulliyyah in understanding Shari'a propositions (hadith and the Qur'an). This thought is still rare in journal articles discussing maqāṣid in Indonesia. Moreover, bin Bayah combined it with the theory of tahqīq al-manāṭ. Therefore, this study uses Bin Bayah's books to explore the method of using maqāṣid in fiqh ḥadīṡ (understanding hadith). As a result, Bin Bayah did not separate maqāṣid from uṣūl fiqh. He mentions 30 frameworks in uṣūl fiqh that can be used with maqāṣid to produce a good understanding of hadith and the Qur'an. To understand hadith texts that are mostly zannīyat, Bin Bayah uses three methods: (1) understanding juz'iyyah propositions (hadith texts) in the corridor of kulliyat propositions which can be in the form of verses of the Qur'an, thematic hadiths, and maqāṣid 'āmmah/ maqāṣid kulliyah, (2) considering the similarities, differences, and changes in the variables mentioned in the naṣṣ and these variables in the present/future life [i'tibar manāṭ], (3) integration of maqāṣid sharī'ah and uṣul fiqh in understanding hadith. [Abdullah Bin Bayah adalah salah satu ulama level internasional dengan multi kepakaran. Ia menawarkan penggunaan maqāṣid kulliyyah dalam memahami dalil syariat (hadis dan Al-Qur’an). Pemikiran tersebut masih asing di artikel jurnal yang membahas maqāṣid di Indonesia. Apalagi bin Bayah menggunakannya bersama dengan teori tahqīq al-manāṭ. Oleh karena itu penelitian ini menggunakan buku-buku Bin Bayah untuk menelusuri metode penggunaan maqāṣid dalam fiqh ḥadīṡ (memahami hadis). Hasilnya, Bin Bayah tidak memisahkan maqāṣid dari uṣūl fiqh. Ia menyebutkan 30 framework dalam uṣūl fiqh yang dapat digunakan bersama maqāṣid untuk menghasilkan pemahaman hadis dan Al-Qur’an yang baik. Untuk memahami teks-teks hadis yang kebanyakan zannīyat, Bin Bayah menggunakan tiga acara: (1) memahami dalil juz’iyyah (teks hadis) dalam koridor dalil kulliyat yang dapat berupa ayat Al-Qur’an, hadis setema, dan maqāṣid ‘āmmah/maqāṣid kulliyah, (2) mempertimbangan persamaan, perbedaan, dan perubahan variabel yang disebutkan dalam naṣṣ dan variabel tersebut di kehidupan sekarang/akan datang [i’tibar manāṭ], (3) integrasi maqāṣid sharī’ah dan uṣul fiqh sebagai konsiderasi sekaligus piranti penggalian hukum dalam memahami hadis dan dalil lainnya.]